Exploring Speaking Activities through the Role-Play Strategy in an English as a Foreign Language Course for Junior High School Students - Maghfiroh, Rizkiana Intan Devi; Ferdiyanto, Feri; Zainuddin, Zainuddin (Journal of English Language and Education, 2026)
Speaking is an important ability in English as a Foreign Language (EFL) education because it allows students to communicate in real-world circumstances. However, many classrooms continue to emphasize grammatical knowledge above communicative practice. This circumstance causes a disconnect between communicative language education concepts and classroom execution. Previous research has demonstrated that role-playing can help students enhance their speaking skills, confidence, and drive. Nonetheless, there has been little research on how role-playing is administered and what types of role-play activities are employed in classroom practice. The purpose of this study is to investigate the implementation of speaking activities using the role-play technique, as well as to identify the various types of role-play activities employed in a junior high school EFL course. A qualitative descriptive design was used. Data were gathered using classroom observations, semi-structured interviews, and documentation. The participants included fourteen junior high school students and one English teacher in an English course at SMP Darul Fawaid Ilmiyah. The data were examined with an interactive qualitative analysis model. The data indicate that role-play activities are carried out in stages, including explanation, modelling, pair discussion, performance, and feedback. Different activities, such as daily discussion and situational talks, promote meaningful contact. The study reveals that role-playing is an excellent way to improve expressive speaking practice in EFL classrooms.